Effector candidates in the secretome of Piriformospora indica, a ubiquitous plant-associated fungus - Rafiqi, Maryam; Jelonek, Lukas; Akum, Ndifor F.; Zhang, Feng; Kogel, Karl-Heinz (Frontiers in Plant Science, 2013)
One of the emerging systems in plant-microbe interaction is the study of proteins, referred to as effectors, secreted by microbes in order to modulate host cells function and structure and to promote microbial growth on plant tissue. Current knowledge on fungal effectors derives mainly from biotrophic and hemibiotrophic plant fungal pathogens that have a limited host range. Here, we focus on effectors of Piriformospora indica, a soil borne endophyte forming intimate associations with roots of a wide range of plant species. Complete genome sequencing provides an opportunity to investigate the role of effectors during the interaction of this mutualistic fungus with plants. We describe in silico analyses to predict effectors of P. indica and we explore effector features considered here to mine a high priority protein list for functional analysis.